Association of CXCR4 expression with coronary collateralization in patients with chronic total coronary occlusion: A nested case–control study. (1st February 2017) - Yang, Chun; Zhu, Wenjin; Han, Xiu; Ma, Aiqun; Bai, Ling; Xu, Feng
Abstract: Objective: CXCR4 signaling contributes to the development and progression of neovascularization. The objective of this study was to investigate whether CXCR4 expression in peripheral CD34 + cells associated with the coronary collateralization (CC) in patients with chronic total coronary occlusion (CTO). Methods and results: We measured CXCR4 expression in peripheral CD34 + cells and assessed its relation with CC in a nested case–control study including 78 cases and 78 matched controls aged 38–69 years, assessed in January 2011 to December 2012 and with at least 1 year of follow-up before the index date. Cases were defined as good coronary collateralization (GCC) according to the Rentrop scoring system (Rentrop score of 2 or 3); for each case, one age-matched control with poor coronary collateralization (PCC) (Rentrop score 0 or 1) was randomly selected from the study participants. Demographic, biochemical, and angiographic variables were collected. In multivariate analysis, the OR (95% CI) of CXCR4 expression was 0.018 (0.017 to 0.020) in patients with GCC versus PCC. Independent effect of CXCR4 expression on CC was (OR 0.012, 95% CI 0.010–0.014) when adjusted for other variables. A nonlinear relationship between CXCR4 expression and CC was observed. The CC degree increased when CXCR4 expression exceeded the turning point (30%) (OR 0.025, 95% CI 0.022–0.028; p < 0.001). When the CXCR4 expression exceeded 75%, increased CXCR4 level could not promoted CC (OR 0.000, 95% CI 0.008–0.007; p = 0.974). Conclusion: Increased CXCR4 level in peripheral CD34 + cells was associated with GCC in patients with CTO.